2021
DOI: 10.1039/d1cp01820e
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of nitrous oxide in hydrated cobalt(i) clusters: a theoretical insight into the mechanistic roles of ligand-binding modes

Abstract: Hydrated cobalt(I) cluster ions, [Co(H2O)n]+, can decompose the inert nitrous oxide molecule, N2O. Density functional theory suggests that N2O can anchor to Co+ of [Co(N2O)(H2O)n]+ through either O end-on (η1−OL)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…Surprisingly, despite the fact that the N 2 O reduction (reaction 6) was not observed experimentally, this reaction is computationally predicted to be highly exothermic for both the 7 Mn(I) clusters (reaction 6a; ΔH 0 °= −55 to −203 kJ mol −1 ) and the 5 Mn(I) clusters (reaction 6b; ΔH 0 °= −118 to −220 kJ mol −1 ) throughout the studied cluster sizes. The electron transfer from Mn(I) toward the bound N 2 O results in its bending with ∠N−N−O ranging from 122°to 138°, similar to the theoretical prediction for the case of hydrated Co(I) clusters 19 for which reactions were observed experimentally. 18 In fact, hydration clusters of the more oxidized divalent Mn(II) ion were also stable and had been experimentally observed in the gas phase.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Surprisingly, despite the fact that the N 2 O reduction (reaction 6) was not observed experimentally, this reaction is computationally predicted to be highly exothermic for both the 7 Mn(I) clusters (reaction 6a; ΔH 0 °= −55 to −203 kJ mol −1 ) and the 5 Mn(I) clusters (reaction 6b; ΔH 0 °= −118 to −220 kJ mol −1 ) throughout the studied cluster sizes. The electron transfer from Mn(I) toward the bound N 2 O results in its bending with ∠N−N−O ranging from 122°to 138°, similar to the theoretical prediction for the case of hydrated Co(I) clusters 19 for which reactions were observed experimentally. 18 In fact, hydration clusters of the more oxidized divalent Mn(II) ion were also stable and had been experimentally observed in the gas phase.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…This size dependence has been rationalized by Siu and co-workers using quantum chemical calculations based on density functional theory (DFT); this theoretical study suggested that the competition of these different reaction mechanisms was attributed to the presence of H 2 O, which could not only act as solvent molecules to stabilize the ionic species but also interact directly as reactant molecules, depending on the characteristic ionic structures of the reaction intermediates with distinct coordination modes. 19 By contrast, the [Mn I (H 2 O) n ] + clusters were the least reactive with N 2 O, giving the smallest absolute rate constants for their reactions. 18 Despite their apparent inertness toward N 2 O, the previous MS study for [Mn I…”
Section: ■ Introductionmentioning
confidence: 99%
“…The yellow and purple clouds illustrate the alpha and beta spin densities, respectively, with an isovalue of 0.06 au. Reproduced and adapted with permission from ref . Copyright 2021, Royal Society of Chemistry.…”
Section: Hydrated Ions In the Gas Phasementioning
confidence: 99%
“…167,168 Microsolvation in hydrated clusters M + (H 2 O) n is expected to change this reactivity considerably. 5 169 The selectivity of these reactions depends on the subtle trends of binding modes of N 2 O toward Co + (H 2 O) n with increasing cluster size n. Figure 10a shows calculated binding energies for N 2 O coordinating to cobalt as well as for a surface-bound N 2 O molecule, which does not form a bond to the metal center. In Figure 10b, hydrated cobalt ion geometries without N 2 O reactant are shown, while Figure 10c provides the most important structures of Co + (H 2 O) 16 (N 2 O).…”
Section: Reactivity Of Hydrated Monovalent Transition Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation